A122 WATER EXCHANGE FACILITATES HIGH CECAL INTUBATION RATE FOLLOWING INCOMPLETE COLONOSCOPY. (4th March 2021) - Lin, T; Tai, T; Parker, B; Taylor, S A; Trasolini, R; Perini, R; Bak, A W
Abstract: Background: Incomplete colonoscopy is a complex problem that negatively affects the success of colon cancer screening programs. Failure to intubate the cecum is associated with a significant risk of missed colorectal cancer and increases costs through missed diagnoses and salvage investigations. Water exchange (WE) colonoscopy is associated with a high rate of patient comfort and cecal intubation (CI) and may be of value in preventing and following up on incomplete colonoscopy. Aims: To estimate effectiveness of WE colonoscopy as initial salvage of incomplete colonoscopy. Methods: All patients referred to the Kelowna Gastroenterology group for incomplete colonoscopy between Jan 2010 to Dec 2019 were included. Demographic, clinical, procedural, and pathological information were collected via retrospective chart review. Patients underwent WE colonoscopy by a single endoscopist. The outcomes evaluated were CI rate, sedation requirements, and adenoma detection. Results: 116 patients met study criteria and underwent WE colonoscopy after a previously failed or incomplete colonoscopy for technical reasons. The mean age was 66 years (range 21–89). 83 (72%) patients were female. 53 (46%) patients had previous abdominal surgery, and 42 (36%) had previous pelvic surgery. 65 (56%) patients had previous bowel disease. 81 (70%) patients had previously incomplete conventional air insufflation (AI) colonoscopy, 9 (8%) patients had previously incomplete WE colonoscopy, and 5 (4%) patients underwent unsuccessful combination of WE and AI colonoscopy. 17 (15%) patients had previously incomplete flexible sigmoidoscopy, and 4 (3%) patients had previously incomplete water immersion colonoscopy. The most common cause of unsuccessful CI was redundant colon (n=39, 34%) followed by strictures/angulations (n=16, 14%). 105 (91%) patients underwent repeat WE colonoscopy only, while 7 (6%) patients had combination WE and AI colonoscopy and 4 (3%) patients had concurrent gastroscopy. CI was successful in 114 (98%) patients and unsuccessful in 2 (2%) patients. 87 (75%) study patients received conscious sedation, 16 (14%) opted for no sedation, and 7 (6%) attempted no sedation then switched to conscious sedation. 5 patients (4%) required general anesthesia. CI was achieved in all 16 unsedated patients. 236 polyps were identified in 79 (68%) patients, 2 (1%) of which were malignant. Conclusions: There is no standardized approach to incomplete colonoscopy. In this cohort of patients with previous failed attempt at colonoscopy, WE as a primary technique was associated with a high success rate with minimal need for general anesthesia and a high rate of polyp detection. A significant rate of colon cancer was identified, similar to that seen in general screening populations. Funding Agencies: None